Usmerjeno zdravljenje okužbe z bakterijo Helicobacter pylori - ali še obstaja druga pot? - Nemanič, Tiva (Zdravniški vestnik, 2016)
Background. Empiric therapy is a mainstay of Helicobacter pylori eradication strategy. With the epidemics of antimicrobial resistance, it is becoming increasingly difficult to select treatment with at least two active antimicrobial agents, needed for cure. Tailored therapy has not been widely accepted in the past, but has lately resurged as a viable alternative. The aim of the study was to review all available studies comparing tailored and empiric therapy in treatment naive adult patients. Methods. PubMed database search was conducted for eligible studies from 1996 to 2016 in English language. All relevant studies were included. Studies that compared standard triple and tailored therapy were included in the meta-analysis. Cumulative relative risk (RR) for eradication success was calculated. Results. Eight studies integrating 2521 participants were evaluated and 7 integrating 1853 patients were included in the meta-analysis. Different tailored approaches were recognized. However, all studies favoured tailored over empiric strategy. Cumulative RR was 1.27 (1.18-1.27) for intention-to-treat (ITT) analysis and 1.28 (1.18-1.38) for per-protocol (PP) analysis. Conclusion. Based on available evidence, tailored therapy is a better alternative to standard triple therapy for eradication of H. pylori. Evidence exist that such approach is also cost effective.
Keywords: bakterijske infekcije; empiric therapy; Helicobacter pylori; izkustveno zdravljenje; tailored therapy; usmerjeno zdravljenje